Immunophenotyping of Acute Lymphoblastic Leukemia in Sudanese Children#x2019;s versus Egyptian children#x2019;s using Flowcyometery (Global Journal of Medical Research, 2021)
Background: Acute lymphoblastic leukemia (ALL) develops rapidly, creating immature white blood cells (WBCs) called lymphoblasts. This type of hematological malignancy is cancer involving blood and bone marrow (BM). It can affect both B and T cell lineage. Here we studied T
Keywords: sudanese egyptian childern; acute lymphoblastic leukemia; flowcytometry